Carpobrotus spp. patches as trap for litter: Evidence from a Mediterranean beach. (December 2021) - Gallitelli, L.; Battisti, C.; Olivieri, Z.; Marandola, C.; Acosta, A.T.R.; Scalici, M.
Abstract: Dunal plants may affect the patterns of deposition of beach litter. In this study, we aimed at evaluating if Carpobrotus spp. patches may act as a litter trap in coastal dune systems. To do so, we counted the number of macrolitter occurring in both Carpobrotus and control (embryo dune vegetation) patches classifying each item into categories according to the Marine Strategy. Totally, we observed a significant difference between litter trapped in Carpobrotus (331 items, representing 62.4% of the total beach litter) and control (199, 37.6%). Plastic fragments were the most trapped items by both Carpobrotus (46.2%) and control patches (47.2%). We also calculated the item co-occurrence, obtaining a random aggregated 'litter community'. The main emerging output is that Carpobrotus patches act as filter in respect to different anthropogenic materials (overall plastics), suggesting that alien plant management actions may contribute to solve beach litter issues as well. Graphical abstract: Unlabelled Image Highlights: Carpobrotus spp. trapped 331 litter items (62.4%) and the control 199 (37.6%). We observed a significant difference between litter trapped in Carpobrotus and in the control. Plastic fragments were the most trapped items by Carpobrotus and control. Dunal vegetation interferes with litter deposition dynamics in coastal ecosystems. Managers removing Carpobrotus could at the same time remove trapped beach litter.